SPECIATION OF ANTIMONY COMPOUNDS WITH HIGH PERFORMANCE LIQUID CHROMATOGRAPHY â HYDRIDE GENERATION - ATOMIC ABSORPTION SPECTROPHOTOMETRY (HPLC-HG-AAS) TECHNIQUE - Herlinawati
Antimony is a non-essential element found in plants, animals and humans. Antimony released into the environment through human activities such as spoilage, mining, smelting and burning of fossil fuels. The toxicity of the antimony compound depends on its shape. Generally antimonite (Sb(III)) is ten times more toxic than antimonate (Sb(V), and inorganic antimony species are more toxic than antimony organic species if distributed in environments, it is necessary to research for the determination of species of antimony compounds for species Sb(III) and Sb(V) because these species are found in environments with different matrices and toxicities. Various methods have been used for the analysis of antimony speciation and its compounds include the determination of Sb(III) and Sb(V) and organic antimony compounds. Most analytical techniques for the separation and detection of antimony species are based on the combination of HPLC methods with elementspecific detectors, such as HG-AAS. Determination with HG-AAS is a sensitive analytical method for Sb metal elements, due to fewer and more selective, so HG (Hydride Generation) combined with AAS detection is preferred for the determination of the elements in hydride form. In this research has been developed high performance liquid chromatographyhydride generation-atomic absorption spectrophotometry (HPLC-HG-AAS) technique for speciation of antimony compounds. The antimony compounds have been analyzed were Sb(III), Sb(V), and trimethyl antimony bromide (TMSb-Br), due to of their wide usage in industries and in daily life. A tetrabutyl ammonium hidroxide (TBA-OH) has been used as ion pairing reagent for the separation of antimony compounds by ion pair-reversed phase (IP-RP) chromatographic technique. The antimony compounds can form ion pair with tetrabutyl ammonium hydroxide with different ion pairing formation constants. Formation ion pair species increase hydrophobicity of the species and can be retented on a non-polar stationary phase. To increase the sensitivity of determination it can be realized by hydride generation (HG) technique, through a gas-liquid separator and a unit of hydride generator merged on-line with an AAS detector. vi Based on the optimum conditions obtained on IP-RP chromatography separation and detection system with HG-QFAAS, IP-RP-HG-QFAAS technique for the separation and detection of antimony compounds on-line system can be realized. IP-RP-HG-QFAAS technique was developed, evaluated and validated can be used not only to study the retention mechanism of antimony compounds of the separation by IP-RP chromatography technique, but also be able to use for separation and determination of the concentrations of antimony compounds in volcanic ash samples. To increase the sensitivity of the measurements, a gas-liquid reactor-separator integrated into the HG-QFAAS system has been successfully prepared. In fact, this gas-liquid reactor-separator is able to increase the sensitivity of determination of Sb ions in solution. The gas-liquid separator used by the mixing technique between the acid, sample, and reductant reagents occur in a coil reaction before going to the gas-liquid separator. The optimum conditions of parameters measurement in the determination of Sb ion species with HG method are influenced by the acid type, the acid concentration, and the reductant concentration have been determined and can increase the measurement of analytical performance simultaneously. The analytical performance obtained is very good, which is shown by repeatability level has been shown by it’s coefficient of variance was 2.33% for the Sb(III) standard concentration 6 ?g.L-1 and 4.40% for the Sb(V) standard concentration 150 ?g.L-1, detection limit of 0.45 ?g.L-1 for the Sb(III) standard and 8.42 ?g.L-1 for the Sb(V) standard with sensitivity (S) 0.07 ?g.L-1 and 1.26 ?g.L-1 for Sb(III) and Sb(V) standard respectively, and linearity for Sb(III) and Sb(V) are 2 - 10 ?g.L-1 and 50 - 250 ?g.L-1 with correlation coeffisien (R2) = 0.9936 and R2 = 0.9942. HG-QFAAS technique can increase the sensitivity measurement than the detection by direct measuring with the AAS. The IP-RP-HG-QFAAS technique developed able to separate of Sb(III), Sb(V), and TMSb(V) species with a good separation performance. The result of this investigation has been shown by the value of fundamental chromatographic parameters obtained. The optimum composition eluent methanol : tetrabutyl ammonium hydroxide (TBAOH) are 0 : 100, containing of 5 mM TBAOH as ion pairing reagent and the eluent pH are 7. The capacity factors (k') obtained for the TMSb(V), Sb(V), and Sb(III) species were 3.69; 4.72; and 8.23 respectively. The values of resolution (Rs) for the separation of TMSb(V)-Sb(V) and Sb(V)-Sb(III) are 0.68 and 1.92 respectively and selectivity (?) for TMSb(V)-Sb(V ) and Sb(V)- Sb(III) are 1.28 and 1.74 respectively, indicate the effectiveness of the developed chromatographic system. The retention mechanism of the antimony compound species specification in the non-polar stationary phase columns is through the interaction of the tetrabutyl ammonium hydroxide ion pair with the stationary phase. This retention mechanism is similar to the known ion exchange mechanism, only the ion exchange reaction in this research takes place dynamically. The developed IP-RP-HG-QFAAS hyphenated technique has been successfully used to separate the antimony compound species in non-polar stationary phase columns and can be detected in the AAS detector. vii The analytic performance obtained good enough represented by the measurement detection limit for each TMSb(V), Sb(V), and Sb(III) species is 201.6 ?g.L-1; 15.67 ?g.L-1; and 271.7 ?g L-1 respectively, repeatibility level shown by it’s coefficient of variance of TMSb(V), Sb(V), and Sb(III) species respectively are 1.21; 2.78; and 4.84% with linearity (concentration range) TMSb(V), Sb(V) and Sb(III) respectively are 100-1000 ?g.L-1, 100-500 ?g.L-1, and 800-1800 ?g.L-1 with correlation coefficient (R2) = 0.9803, R2 = 0.9919 and R2 = 0.9654. Hyphenated technique IP-RP-HG-QFAAS developed has been applied for speciation analysis of antimony compounds in volcanic ash. The measurement of it’s accuracy is very good, illustrated by the recovery percentage > 92% for determination of volcanic ash samples, proved this hyphenated technique is good to be applied for speciation of antimony compounds analysis